Pemahaman Manajemen Perusahaan Tentang Peraturan Perpajakan Terhadap Kepatuhan Wajib Pajak Badan Di Kota Bandar Lampung (Study Kasus di Kota Bandar Lampung) - Thontowie Dauli; Andrian Wijaya; Chairul Anwar (Universitas Bandar Lampung (UBL), 2012)
Bandar Lampung is one of a growing city in the economic field in the province of Lampung. One economic sector to support the development of such companies is corporate taxes. But the company is still a lack of awareness of the importance of understanding the tax laws and regulations, and compliance with corporate taxpayers understand. Yet by understanding the tax laws and compliance with corporate taxpayers, the company will also understand the obligations and rights as a taxpayer. The problems that the authors point out is how the understanding of the companys management of tax regulations on tax compliance entities in Bandar Lampung. The method used in this paper is a field of research questionnaires. And methods of analysis in this study is the method of qualitative analysis and quantitative analysis. From the analysis of qualitative and quantitative analysis and discussion, it can be concluded that the understanding of the companys management in the city of Bandar Lampung on tax laws on tax compliance bodies have a positive relationship, in which the Taxpayer Compliance significantly influenced by the understanding of the Corporate Management Tax Regulation.